SISTEM INFORMASI ADMINISTRASI NILAI SMP NURUL ULUM SEMARANG BERBASIS MULTIUSER - Muhammad Sidik; Iwan Koerniawan (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2018)
The purpose of this final project besides fulfilling one of the requirements for completing undergraduate education at the Electronic and Computer High School (STEKOM) is also to facilitate the recording and processing of report cards with computer applications at the Nurul Ulum Middle School Semarang. So it has benefits for managers, namely improving report card processing to be faster and improve work efficiency. Formulation of the problem of how to overcome inaccuracy in the processing of student grades at SMP Nurul Ulum and how to design information systems that can be processed together in entering grades in one computer database.The research used observation, interview and literature study methods. In preparing the report using several designs: context diagrams, data flow diagrams (DFD), normalization, entity relationship diagrams (ERD) and program implementation.The results of the analysis of making value administration information systems can reduce the problems that exist in Nurul Ulum Junior High School Semarang and provide easy value information services for teachers and create a database that is generated can be archived safely. Software used: in the preparation of this thesis the author uses Visual Basic 6.0 programming with MYSQL database.